A comparison of airway maintenance by cuffed Oropharyngeal airway (COPA) and laryngeal mask airway (LMA) in spontaneously breathing adult patients - Zia, Ashraf; Chaudhry, Tahir; Hussain, Riaz; Ghalani, Tafoorul Islam (Annals of King Edward Medical University, 2016)
In this study total hundred patients wee included. Fifty (group I) were subjected to COPA device for airway maintenance and in other fifty (group II) LMA was used. In this study first attempt successful insertion rate in group I was 90% while in group II it was 94%. However statistical analysis showed no significant different in both groups. Regarding maneuvers needed to maintain smooth breathing in group I head tilt was used in 2 %. It is significantly high in group I than in group II. Laboured breathing was seen in 6% in group I while 2% in group II. There was no significant difference in both groups. According to this study LMA is better in all respect as it is easier to insert and better fit in.